2007
DOI: 10.1073/pnas.0701768104
|View full text |Cite
|
Sign up to set email alerts
|

Sacred bounds on rational resolution of violent political conflict

Abstract: We report a series of experiments carried out with Palestinian and Israeli participants showing that violent opposition to compromise over issues considered sacred is (i) increased by offering material incentives to compromise but (ii) decreased when the adversary makes symbolic compromises over their own sacred values. These results demonstrate some of the unique properties of reasoning and decision-making over sacred values. We show that the use of material incentives to promote the peaceful resolution of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
249
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(270 citation statements)
references
References 15 publications
10
249
0
4
Order By: Relevance
“…In surveys of two Moroccan communities associated with militant jihad (20), and where we had done intensive anthropological fieldwork, we used the same fusion measure as Whitehouse et al (1) and a sacred value measure adapted from a previous publication in PNAS (14). We found that that fusion with family-like groups may drive costly sacrifices expressed, for example, in willingness to use violence…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In surveys of two Moroccan communities associated with militant jihad (20), and where we had done intensive anthropological fieldwork, we used the same fusion measure as Whitehouse et al (1) and a sacred value measure adapted from a previous publication in PNAS (14). We found that that fusion with family-like groups may drive costly sacrifices expressed, for example, in willingness to use violence…”
mentioning
confidence: 99%
“…As Darwin surmised in The Descent of Man (11), it is not merely commitment to a tribe of imagined kin but also to its "morality" that instills "the spirit of patriotism, fidelity, obedience, courage, and sympathy" with which winning groups are better endowed in history's spiraling competition for survival and dominance. Studies across cultures suggest that the strongest forms of primary group identity are bounded by sacred values (12), often in the form of religious beliefs or transcendental ideologies (13), which leads some groups to prevail because of nonrational commitment from at least some of its members to actions that drive success independent-or all out of proportion-from expected rational outcomes (14). For such "devoted actors," rightness of in-group cause often leads to intractable conflicts with out-groups that become immune to the give-and-take common to "business-like" negotiations (15).…”
mentioning
confidence: 99%
“…Research shows that when individuals hold some values, certain commitments and relations to be sacred, they may not reason instrumentally, and thus they fail to make trade-offs (Tetlock 2003). Under these circumstances, established penalties or offered motives in policy programmes have no traction on their choices (Tetlock 2003;Ginges et al 2007;Berns et al 2012). The elephant overrides the rider.…”
Section: Human Brain Sacred Values and Conservationmentioning
confidence: 99%
“…Indeed, values are doubtless a greater contributor to many human conflicts than are disputes over evidence (Ginges et al 2007), and in this context it is noteworthy that humanwildlife conflicts in conservation are often styled as human-human conflicts (Marshall et al 2007;Redpath et al 2013). None of this is surprising, but it highlights that any evidence, as might emerge from neuroscience, regarding the way people define and respond to values could be helpful when they are the nub of conservation issues.…”
Section: Human Brain Sacred Values and Conservationmentioning
confidence: 99%
“…For many Israelis, for example, one such value is the right to occupy the West Bank, whereas for many Palestinians it is the right to return to the villages from which they were expelled. In fact, Atran has found that financial offers to compromise on these sacred values makes them even more entrenched 10 .…”
Section: The Ritual Mindmentioning
confidence: 99%